EFEKTIVITAS PEMANFAATAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) - Depniliza Depiani (Manajer Pendididikan, 2015)
The purpose of this study was to evaluate: the utilization of School Operational Assistance. In this study the authors used a qualitative approach in which the evaluative researchconducted is part of management systems. Subjects were principals, committee treasurer, school committees and teachers. Data collection techniques are observation, interviews and documentation. The results showed that the first: reading books in the library has purchased many of School Operational Assistance. Second, School Operational Assistance made effective school exams. Third, the absence of a high dropout rate and the spirit of learning. Fourth, the use ofSchool Operational Assistance funds for the purchase of consumables to be effective. Fifth, payment Paying be very effective. Sixth, School Operational Assistance help extracurricular activities can be effective.Keywords: utilization, school operational assistance.